Study of LRRK2 variation in tauopathy: Progressive supranuclear palsy and corticobasal degeneration. Issue 1 (6th October 2016) - Sanchez‐Contreras, Monica; Heckman, Michael G.; Tacik, Pawel; Diehl, Nancy; Brown, Patricia H.; Soto‐Ortolaza, Alexandra I.; Christopher, Elizabeth A.; Walton, Ronald L.; Ross, Owen A.; Golbe, Lawrence I.; Graff‐Radford, Neill; Wszolek, Zbigniew K.; et al.
ABSTRACT: Background: Mutations in the leucine‐rich repeat kinase 2 gene ( LRRK2) are the most common genetic cause of Parkinson's disease (PD). Unexpectedly, tau pathology has been reported in a subset of LRRK2 mutation carriers. Methods: To estimate the frequency of pathogenic LRRK2 mutations and to evaluate the association of common LRRK2 variants with risk of primary tauopathies, we studied 1039 progressive supranuclear palsy (PSP) and 145 corticobasal degeneration patients from the Mayo Clinic Florida brain bank and 1790 controls ascertained at Mayo Clinic. Sanger sequencing of LRRK2 exons 30, 31, 35, and 41 was performed in all patients, and genotyping of all 17 known exonic variants with minor allele frequency >0.5% was performed in patients and controls. Results: LRRK2 mutational screening identified 2 known pathogenic mutations (p.G2019S and p.R1441C), each in 1 PSP patient, the novel p.A1413T mutation in a PSP patient and the rare p.R1707K mutation in a corticobasal degeneration patient. Both p.A1413T and p.R1707K mutations were predicted damaging by at least 2 of 3 prediction programs and affect evolutionary conserved sites of LRRK2 . Association analysis using common LRRK2 variants only showed nominal association of the p.L153L variant with PSP. Conclusions: Our study confirms the presence of pathogenic and potentially pathogenic LRRK2 mutations in pathologically confirmed primary tauopathies, albeit with low frequency. In contrast to PD, common LRRK2 variants do not appear to play a major role in determining PSP and corticobasal degeneration risk. © 2016 International Parkinson and Movement Disorder Society.